The effect of literature circle on varied reading comprehension - Rahman, Abdul (Yayasan Cendekiawan Indonesia Timur, 2022)
This research was conducted to know the effect of using the Literature circle to improve the students’ reading comprehension. It covered students’ literal comprehension, inferential comprehension, and critical comprehension. This research was designed into two groups; the Experimental group and Control group. Each group consisted of 20 students. The sample was chosen by using the simple random technique used lottery technique. The data were collected through multiple-choice reading tests both in the experimental group and control group namely pre-test and post-test then analyzed by using an independent-sample t-test and One way ANOVA. The result of the research showed that (1) the use of a literature circle was more effective than the directed reading activity method in improving students reading comprehension. It was revealed that the students’ improvement in post-test with a mean score of 65.30 was better than the mean score of pre-test 52.85 in the experimental group. There was also a statistically significant difference between the mean score of the post-test of the experimental group and the control group in each level of comprehension. The largest different was on inferential level (67.50 > 56.50), followed by literal level (65.50 > 64.00), and then critical level (61.50 > 60.50). (2) based on the result of one-way ANOVA from the three levels of reading comprehension in the experimental group, none of them is significantly different, or the three levels of reading comprehension almost have the same average score (l = i = c).